Gene Expression Signatures Point to a Male Sex-Specific Lung Mesenchymal Cell PDGF Receptor Signaling Defect in Infants Developing Bronchopulmonary Dysplasia. Issue 1 (December 2018) - Fulton, Christina; Cui, Tracy; Goldsmith, Adam; Bermick, Jennifer; Popova, Antonia
Abstract Male sex is a risk factor for development of bronchopulmonary dysplasia (BPD), a common chronic lung disease following preterm birth. We previously found that tracheal aspirate mesenchymal stromal cells (MSCs) from premature infants developing BPD show reduced expression of PDGFRα, which is required for normal lung development. We hypothesized that MSCs from male infants developing BPD exhibit a pathologic gene expression profile deficient in PDGFR and its downstream effectors, thereby favoring delayed lung development. In a discovery cohort of 6 male and 7 female premature infants, we analyzed the tracheal aspirate MSCs transcriptome. A unique gene signature distinguished MSCs from male infants developing BPD from all other MSCs. Genes involved in lung development, PDGF signaling and extracellular matrix remodeling were differentially expressed. We sought to confirm these findings in a second cohort of 13 male and 12 female premature infants. mRNA expression of PDGFRA, FGF7, WNT2, SPRY1, MMP3 and FOXF2 were significantly lower in MSCs from male infants developing BPD. In female infants developing BPD, tracheal aspirate levels of proinflammatory CCL2 and profibrotic Galectin-1 were higher compared to male infants developing BPD and female not developing BPD. Our findings support a notion for sex-specific differences in the mechanisms of BPD development.